Do Indonesian firms practice target capital structure? A dynamic approach - Haron, Razali (Emerald Group Publishing Limited, 2016)
This study investigates the dynamic aspects of capital structure particularly on the existence of target capital structure, the speed of adjustment and the factors influencing target capital structure of Indonesian firms. This study finds that Indonesian firms do practice target capital structure and the capital structure decision is influenced by firm specific factors like profitability, business risk, firm size, liquidity and share price performance due to time varying factors. Pursuing target capital structure and identifying the influencing factors may gear the firm to value maximization thus is indeed a paramount move for a firm to ensure sustainability and competitiveness and firms in Indonesia demonstrate that in this study.